Ethnic Disparities in Hepatitis B Virus Infection Among 1 Million Reproductive-Age Couples Preparing for Pregnancy in the Rural Yunnan, China: A Population-Based Cross-Sectional Study - Jing, Wenzhan; Yuan, Yanling; Liu, Min; Ye, Hanfeng; Kong, Cai; Liu, Jue; Wu, Yu (Frontiers in Medicine, 2022)
Introduction Hepatitis B is a potentially life-threatening liver infection caused by hepatitis B virus (HBV) and China has the largest disease burden. We aimed to understand ethnic disparities in HBV infection among married reproductive-age couples planning for pregnancy in Yunnan, a multiethnic province in Southwest China, to increase health equities within the hepatitis response in China. Methods A population-based cross-sectional study was performed. Couples aged 20-49 years in rural Yunnan were enrolled through the National Free Preconception Health Examination Project from Jan 2014 to Dec 2019. HBsAg-positive couples were defined as couples in which one or both of them were HBsAg-positive, and HBsAg- & HBeAg-positive couples were defined as HBsAg-positive couples in which one or both of them were HBeAg-positive. The HBV prevalence of positive couples was estimated by ethnicity. Multivariate logistic regression analyses were used to assess the association between ethnicity and HBsAg status. Results Overall, 63,513 of 1,060,643 couples (5.99%, 95% CI 5.94%-6.03%) were HBsAg-positive couples, and 15,898 of 63,513 HBsAg positive couples (25.03%, 95% CI 24.69%-25.37%) were HBsAg- & HBeAg-positive couples in rural Yunnan. The highest prevalence of HBsAg-positive couples was in the Miao & Miao and Zhuang & Zhuang ethnic groups (12.04% and 9.76%), and the risk of HBV infection of wives/husbands in these ethnic groups was significantly higher than that in the Han & Han ethnicity. Additionally, the HBsAg prevalence in wives/husbands increased with the positive status of HBsAg and HBeAg of their spouses. Conclusion The HBV prevalence in reproductive-age couples was intermediate (6% of 1 million couples) in rural Yunnan, China, with the highest in the Miao & Miao ethnicity and Zhuang & Zhuang ethnicity. There are still large ethnic disparities in HBV infection in China. Therefore, China should make great efforts, especially giving priority to ethnic minorities and taking positive couples as an important unit of care, to equitably eliminate HBV intrafamilial transmission.